PENGEMBANGAN PEMBELAJARAN IPS DENGAN MEDIA KARTU BELAJAR BAGI GURU SD/MI/ SDN I PALAPA DIKECAMATAN DURIAN PAYUNG - Listari, Rida (LPPM STKIP PGRI Bandar Lampung, 2020)
Social studies teaching and learning process in schools is generally considered unattractive, as a result of which many school children are not interested in studying social studies subjects. In addition, there is an assumption that social studies subjects are not so important so that students in the teaching and learning process are not so serious in following them. Some indicators that show that the social studies subject is not interesting or important is that the values ​​of social studies lessons are not that high, and the Social Science program in SD is considered the number two program after Natural Sciences. Therefore, to accelerate understanding and avoid misunderstanding, appropriate approaches and teaching media are needed, according to the mental maturity level of students. The approach recommended in KTSP is a contextual approach including the medium. Educational media does not only include electronic media but can be simple media that can be prepared by teachers. One of the learning media that can be used is learning cards. In the training on the use of Karu Belajar media in social studies teaching and learning at SDN I Palapa Tanjung Karang, there were 35 participants from 40 registered participants. Participants believed that Study Cards were simple, easy to make and use and could increase student activity in social studies learning.